ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI CENGKEH DI KECAMATAN DAKO PEMEAN KABUPATEN TOLITOLI - Nurmala Nurmala; Made Antara; Hj Hadayani (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This research was conducted at Dungingis and Kapas Villages, Dako Pemean Sub District, Tolitoli Regency. The objective of the research is to determine the influence of production input uses and their efficiency in clove farming.  The inputs included number of productive trees, urea fertilizer, ZA fertilizer, phonska fertilizer, and labor. This research use Slovin equation in determining the number of respondents. The number of respondents was 75 clove farmers. Data was analyzed using multi linier function analysis of Cobb Douglas. The results of the research showed that the independent variables (Xi) such as the number of productive trees (X1), urea fertilizer (X2), ZA fertilizer (X3), phonska fertilizer (X4), and labour (X5) simultaneously had significant effect on the production as the dependent variable (Y). The coefficient of determination was 0.975 indicating that the fluctuation in the clove production can be explained by its independent variables by 97.5% while the other variables not including in the model was by 2.5%.  The efficiency analysis showed that the k value of the variable of the productive tree number (X1)was < 1 suggesting that this variable is not efficient from the point of price view. By contrast the other variable such as urea fertilizer (X2), ZA fertilizer (X3), phonska fertilizer (X4) and labor (X5) had k values> 1 indicating that the use of these inputs is not efficient yet from the point of price view, as well. Keywords :Clove production, efficiency, and production input.